POTENTIAL OF TANNIN COMPOUNDS FROM LAMPUNG COFFEE BEAN SKIN EXTRACT AS NATURAL DYES FOR COTTON FABRICS - Fauziyah, Napilah
The study of natural dyes from plant extracts has been carried out by many researchers. One source of natural dyes that can be used is the skin of coffee beans. Currently, Lampung coffee bean skin have not been widely used by the local community so they tend to become solid waste. In this research, the extraction process of tannin compounds from Lampung coffee bean skins has been carried out using conventional methods. Coffee bean skin samples were extracted by maceration as much as 600 g using methanol for three days, then concentrated using a rotary evaporator at a temperature of 40oC at a speed of 60 RPM. The compounds contained in the coffee bean skin extract were analyzed qualitatively by carrying out phytochemical screening tests and thin layer chromatography (TLC), as well as infrared spectrum measurements to identify the vibrational peaks of functional groups that are typical for tannin compounds. The potential of coffee bean skin extract as a natural dye has been tested on mori primisima cotton cloth using three types of mordant, namely KAl(SO4)2.12H2O, Ca(OH)2, and FeSO4. Three coloring methods were used in this study, namely pre-mordanting, simultaneous mordanting, and post-mordanting methods. The potential of Lampung coffee bean skin extract as a natural dye was evaluated by measuring color strength and color fastness to washing. The results showed that type and method of mordanting affected color produced and strength of color on the fabric. Visually, cotton cloth stained with coffee bean skin extract without mordant (control) produced a faded brown or beige color. For fabrics treated with KAl(SO4)2.12H2O mordant, the color of fabric was relatively similar to the color of control fabric. Each of the fabrics treated with Ca(OH)2 and FeSO4 mordant has a darker color than the fabrics using KAl(SO4)2.12H2O mordant. This result is confirmed by K/S value obtained through measurements using a Minolta spectrophotometer. The highest average value of color strength (K/S) was observed in cotton fabrics treated with FeSO4 mordant and the lowest K/S values were observed in cotton fabrics that did not use mordant in the dyeing process. Among three mordanting methods, the post-mordanting method produces the strongest color intensity and even color compared to pre-mordanting and simultaneous mordanting methods. This is indicated by the highest K/S value. The color fastness test of fabric was carried out using a Lauder-o-meter. The assessment of the results of testing color fastness of fabric after washing and before washing was measured using a gray scale, while